Effect of intermittent high-intensity sonication and temperature on barley steeping for malt production. (July 2018) - Carvalho, Gisandro Reis de; Polachini, Tiago Carregari; Darros-Barbosa, Roger; Bon, José; Telis-Romero, Javier
Abstract: Barley malt production comprises three main steps: steeping, germination, and drying. Ultrasound technology has been widely studied to find ways to improve mass transfer in food processes and, consequently, to reduce process times. So, this study evaluated the effect of temperature and the intermittent application of ultrasound on the steps involved in barley hydration. The barley hydration was carried out at 10, 15, 20, and 25 °C with and without the application of 0.75 W/mL and 1.5 W/mL of nominal power density at 20 kHz. The ultrasonic energy delivered was measured in the same conditions as the steeping process using a calorimetric method, taking distinct differential volume measurements throughout the hydration medium. The ultrasonic energy delivered presented average values of 51.1 W at 750 W and 84.7 W at 1500 W nominal power. Ultrasound application increased both water uptake rates and equilibrium moisture content as shown by the Peleg and Weibull-exponential model parameters, with the latter showing better adjustment ( R a d j 2 >0.953 and NRMSE <5%). Applying ultrasound also significantly reduced the time required to achieve the conventional moisture level required for barley germination: 29% and 44% at controlled temperatures of 20 °C and 25 °C, respectively. Highlights: The effect of temperature and input power on barley hydration was studied. A new approach to determine the acoustic fields was reported. Hydration processes were well-fitted to both the Weibull and Peleg models. Ultrasound enhanced both water uptake and equilibrium moisture content. Ultrasound reduced the hydration time required for barley germination by up to 44%.